Adsorption tetracycline from aqueous solution using a novel polymeric adsorbent derived from the rubber waste - Muhammad Aliyu; Abdullah, Abdul Halim; Mohamed Tahir, Mohamed Ibrahim (Elsevier, 2022)
Background: Tetracycline (TC) is an antibiotic used by humans and animals that enters sewage in the form of a parent compound, which can endanger aquatic organisms and human health due to bioaccumulation, non-biodegradability, and high persistence. Methods: Herein, the rubber waste, namely dipping tank coagulum (DTC), collected from a glove manufacturing factory were converted into a novel polymeric-adsorbent via a simple sulfonation reaction with concentrated sulphuric acid. FT-IR, EDX, FESEM, and BET techniques were used to characterize the rubber waste before and after modification. The adsorbents were used to remove TC from aqueous solution via batch adsorption method. The effects of solution pH, contact time, adsorbent dose, and initial concentration of TC solution on the TC adsorption onto adsorbent were investigated. Significant findings: The highest TC removal (90%) was obtained at optimum condition of 30 mg MRW, 30 mg/L TC, pH 3 and 25 °C after 5 h of contact time. The adsorption data fitted the Langmuir isotherm, indicating a monolayer adsorption with the maximum adsorption capacity of 76.33 mg/g and found to be compatible with the pseudo-second-order kinetic model. Furthermore, the thermodynamic data (ΔH° = -4.01 kJ/mol, ΔG° = -8.95 to -9.20 kJ/mol,) showed that the adsorption process was exothermic and spontaneous at studied temperatures.After ten cycles of the repeated adsorption-desorption procedure, MRW retained 90% of the removal percentage. MRW demonstrated an excellent adsorption capacity for removing TC from real water samples (municipal wastewater and tap water) Finally, this study indicates that rubber waste could be used as a promising low-cost adsorbent for the adsorption of pharmaceuticals from water and wastewater.